Strategi Efektif dalam Kegiatan Penyusutan dan Pemeliharaan Arsip di Lembaga Kearsipan UPI - Fadilah, Syifa Diani; Silvana, Hana; Khoerunnisa, Lutfi (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2025)
Archives have a very important role, so an institution must have good archive management starting from archive creation to archive shrinkage. This article discusses effective efforts or strategies in archive shrinkage and archive maintenance activities at the Archival Institute of Universitas Pendidikan Indonesia (UPI). The purpose of this research is to find out the strategies or methods carried out by the institution in the depreciation and maintenance of archives. The research method in this article uses a qualitative approach and descriptive analysis of literature review, and data collection techniques are obtained through observation, interviews, and literature study. Interviews were conducted with related archivists. Overall, this research focuses on best practices that can be done in archive management to improve efficiency and effectiveness of sustainability. The strategies discussed include paying attention to the Archive Retention Schedule, the process of destroying archives is also certainly based on predetermined rules, as well as efforts to maintain physical and digital archives that have been carried out by the UPI "University Archives" institution. The research results from the implementation of this strategy show that the archives have proven to be well maintained, increase efficiency, and have the potential for an archive institution to get a better award or accreditation from ANRI. This article is expected to make an important contribution in sharing best practices in archival information management. Thus, related parties can jointly develop and improve problems that become deficiencies in information management, especially archives, so that in the future it can always run well in supporting activities in any archival institution, be it from government or private agencies, certain companies, to universities.